2007
DOI: 10.1123/apaq.24.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Responsibilities and Training Needs of Paraeducators in Physical Education

Abstract: This study describes responsibilities and training needs of paraeducators in physical education. Paraeducators (n =138) employed in 34 midwestern schools received a 27-item questionnaire. Of the 138 paraeducators contacted, 76 responded, resulting in a 55.1% response rate. Only 16% of the total respondents (n = 76) reported receiving specific training in physical education; however, 68 (90%) indicated a willingness to be trained. Less than half (n = 29, 38%) indicated participating in physical education by esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
1
14
0
2
Order By: Relevance
“…Una formación específica y conocimientos acerca de la discapacidad son determinantes para la inclusión (Avramidis, Bayliss, y Burden, 2000;Vickerman, y Coates, 2009), de manera que aquellos profesores que no hayan tenido una formación previa adecuada no se verán preparados para atender a la diversidad en el aula (Davis, Kotecki, y Oliver, 2007;Rust, y Sinelnikov, 2010), pudiendo ello estar relacionado con su percepción de autoeficacia a tenor de los resultados obtenidos en la presente investigación.…”
Section: Discussionunclassified
“…Una formación específica y conocimientos acerca de la discapacidad son determinantes para la inclusión (Avramidis, Bayliss, y Burden, 2000;Vickerman, y Coates, 2009), de manera que aquellos profesores que no hayan tenido una formación previa adecuada no se verán preparados para atender a la diversidad en el aula (Davis, Kotecki, y Oliver, 2007;Rust, y Sinelnikov, 2010), pudiendo ello estar relacionado con su percepción de autoeficacia a tenor de los resultados obtenidos en la presente investigación.…”
Section: Discussionunclassified
“…Although paraprofessionals are assumed to be capable of providing much-needed assistance during PE for students with disabilities (Horton, 2001), there was just one study (Murata & Jansma, 1997) on the effects of paraprofessionals on inclusive PE. In addition, after conducting a survey of paraprofessionals' training needs in PE, Davis, Kotecki, Harvey, and Oliver (2007) found that only 16% of the respondents received specific training in PE. The results of this study indicated that support in the form of trained paraprofessionals along with trained peer tutors not only aided students with disabilities but prevented their inclusion from disrupting the learning of peers without disabilities.…”
Section: Paraprofessionalsmentioning
confidence: 99%
“…Focus on student and stakeholder perspectives has highlighted the impact of teacher attitudes towards inclusion and students with SEN (Hardin, 2005;Morley, Bailey, Tan, & Cooke, 2005;Smith & Green, 2004;Smith, Arthur, McKelvie, & Kodis, 2004), the behavior of disabled and non-disabled students in mainstream PE (Goodwin & Fitzgerald, 2009;Place & Hodge, 2001), levels of support offered and received (Davis, Kotecki, Harvey, & Oliver, 2007;Haegele & Kozub, 2010) and non-disabled peers' views and perspectives (Sato, Hodge, Murata, & Maeda, 2007;Slininger, Sherrill, & Jankowski, 2000;Verderber, Rizzo, & Sherrill, 2003). Furthermore, recent studies have begun to examine how the opinions of stakeholders, including teachers, parents and policy makers, can influence those of others including children (Fitzgerald, 2012).…”
Section: Introductionmentioning
confidence: 99%